2014
DOI: 10.1038/ncb2994
|View full text |Cite
|
Sign up to set email alerts
|

Increased microtubule assembly rates influence chromosomal instability in colorectal cancer cells

Abstract: Chromosomal instability (CIN) is defined as the perpetual missegregation of whole chromosomes during mitosis and represents a hallmark of human cancer. However, the mechanisms causing CIN and its consequences on tumor growth are largely unknown. We identify an increase in microtubule plus end assembly rates as a fundamental trigger for CIN in CRC cells. This trigger is mediated by overexpression of the oncogene AURKA or by loss of the tumor suppressor gene CHK2, a genetic constitution found in 73% of human col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
284
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(312 citation statements)
references
References 57 publications
24
284
4
Order By: Relevance
“…Pointing towards a similar direction, the mutant variant of PTPRD (genetic aberrations in ∼7% of breast cancers 2) encoding the protein tyrosine phosphatase receptor type delta was also strongly associated with high numbers of mutated genes in breast cancer. PTPRD has been shown to act as tumour suppressor 49 and impairs function of Aurora A 50, a protein that has been shown to modulate genomic stability 51. Last but not least, the mutated variant of the putative breast cancer oncogene NF1 (genetic alterations in ∼5% of breast cancers 2) correlated with a high abundance of mutated genes in our study.…”
Section: Discussionsupporting
confidence: 54%
“…Pointing towards a similar direction, the mutant variant of PTPRD (genetic aberrations in ∼7% of breast cancers 2) encoding the protein tyrosine phosphatase receptor type delta was also strongly associated with high numbers of mutated genes in breast cancer. PTPRD has been shown to act as tumour suppressor 49 and impairs function of Aurora A 50, a protein that has been shown to modulate genomic stability 51. Last but not least, the mutated variant of the putative breast cancer oncogene NF1 (genetic alterations in ∼5% of breast cancers 2) correlated with a high abundance of mutated genes in our study.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, recent studies took advantage of the fact that aberrant microtubule dynamics driving CIN (discussed above) can be modulated to test the role of CIN in tumourigenesis. One study found that limiting CIN in a mouse model of CRC lead, seemingly counter-intuitively, to increased tumour growth (Ertych et al 2014). However, in light of the knowledge that CIN and aneuploidy can carry a fitness cost, this is perhaps not surprising.…”
Section: Modulating Cin Levels In Cancer For Therapeutic Benefitmentioning
confidence: 96%
“…For example, hyperstable microtubules or increased microtubule assembly rates can promote incorrect chromosome-spindle attachments, lagging chromosomes and aneuploidy (Fig. 1B) (Bakhoum et al 2009a, Ertych et al 2014. Defects in the mitotic checkpoint, also known as the spindle assembly checkpoint (SAC), a cellular surveillance mechanism that ensures mitosis cannot complete until all chromosomes are correctly attached to the mitotic spindle, have also been proposed to contribute to CIN.…”
Section: Mechanisms Driving Chromosomal Instabilitymentioning
confidence: 99%
“…4 Most recently, we have revealed that an increase in microtubule plus end assembly rates within mitotic spindles is not only frequently detected in chromosomally unstable cancer cells, but can also act as a trigger for CIN. 5 Thus, it is of utmost interest to identify the genetic alterations that are responsible for an increase in microtubule plus end polymerization in human cancer cells. As a very first step into this direction we found that loss of the tumor suppressor CHK2 or gain of the oncogene AURKA can result in increased microtubule assembly rates during mitosis.…”
Section: Introductionmentioning
confidence: 99%